IDENTIFICATION OF SPRING IN EAST LAMPUNG - hari perdana, rudi; Eko Susilo, Gatot; Romdania, Yuda (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Water is the source for life. Earth is called the blue planet, as water covers three-quarters of Earth's surface. It's just that most of the sea water (salt water).  Generally, the condition springs in Indonesia experienced a decline in the amount and debit, were damaged in the catchment area and the surrounding environment. To determine the existence of water resources, necessary to identify water resources. This research is to identify the sources of springs in knowing the status of water resources.          The primary data collection is done by identifying the condition of land cover in the catchment area, the condition of the springs, the condition of land cover in a radius of 200 m, the performance of the fountain, the critical level of water catchment areas, the critical level of water catchment areas, the critical level of a radius of 200 m, utilization springs, and the dependence of communities on water resources. While the collection of secondary data obtained from BPLHD Kab. East Lampung in the form of water quality data from 12 springs. Spring Water Quality Analysis using WQI Malaysia with graphic works of Dr. GatotEkoSusilo, S.T., M.Sc.          From the calculations, the average value of the 12 WQI water source is 95.1, meaning that all 12 springs are so richly used by people for drinking, bathing, cooking and others. The 12 water spring in the district of Batang Among them there are 5 springs, in the district of Marga Tiga there are 5 springs, in the District of Sri Bawono there is one source of water, and in District Jabung there is one source of water. Keywords: Water, Water Quality, East Lampung Spring Water, Water            Quality Index Malaysia